Contribuições morfoanatômicas, estudo fitoquímico e de potencial alelopático, antioxidante e antibacteriano do extrato alcoólico e frações de Piper tuberculatum Jacq. (Piperaceae) - (:unkn) unknown (Universidade Federal do Amazonas, 2019)
The genus Piper has ecological, economic and therapeutic importance. Studies of species extracts from this group have shown a diversity of metabolites with remarkable biological activities and many are traditionally used in folk medicine. However, due to the great morphological similarity between species, identification and collection errors are common. Therefore, in-depth taxonomic studies are required. Piper tuberculatum Jacq. It is a species widely used in the treatment of respiratory and digestive diseases. Among its constituents are phenolic compounds, flavonoids, amides, tannins, phytosterols, phenylpropanoids and terpenoids, to which various biological activities are attributed. However, there are no studies on its allelopathic potential. This paper describes the morphoanatomic and histochemical characteristics of P. tuberculatum leaf, as well as the phytochemical profile, allelopathic, antioxidant and antibacterial potential of its crude extract and fractions. Leaves of P. tuberculatum were fixed, cross-sectioned and subjected to classical morphoanatomic and histochemical analyzes. The phytochemical profile of crude extract (EB) and hexane (FH), chloroform (FC), ethyl acetate (FAE) and remnant (FR) fractions were analyzed by colorimetry and high performance liquid chromatography (HPLC). Allelopathic potential was investigated by germination and growth measures, antioxidant activity by phosphomolybdenum complex reduction method and antibacterial activity by disk diffusion. The leaf of P. tuberculatum are simple, with elliptic shaped, entire margin, attenuated-acuminate apex, brochidodrome venation and asymmetric blade, mainly at the base. Morphological characteristics similar to those recorded in the genus. Grouped subepidermal idioblasts distributed on the surface of the adaxial face and close to vascular bundles were observed. This pattern of distribution was first described in Piper. Histochemical tests have shown that phenolic compounds are produced in the subepidermal layers and mesophyll cells, mainly palisade parenchyma. In colorimetric tests, phenolic compounds, flavonoids, tannins, anthocyanidins and phytosterols were quantified. Already by HPLC, the flavonoid vitexin was identified and quantified. The EB and its fractions showed proven allelopathic activity, mainly for EB, FC and FAE at concentrations of 500 μg / mL, which significantly decreased the Germination Speed Index (GSI) and the growth of the tested species. Such effect may be associated with vitexin. None of the samples exhibited antioxidant activity equal to or greater than ascorbic acid standard. Only FAE at 100 mg / mL showed antibacterial activity. Therefore, this work can add significant value for future studies with P. tuberculatum and serve as a basis for taxonomy, phytochemistry and other biological potentials associated with the genus Piper. Especially in relation to allelopathic potential and some taxonomic characteristics that were first described here.
Morfoanatomic contributions, phytochemical study and allelopathic, antioxidant and antibacterial potential of alcoholic extract and fractions of Piper tuberculatum Jacq. (Piperaceae)
Keywords: Fenóis; Germinação; Histoquímica; Ciências Ambientais; Aleloquímicos; Compostos Fenólicos; Germinação e Crescimento; Histoquímica; Idioblastos Secretores